Evolution of Regional Disparities in Poland - Czyż, Teresa; Hauke, Jan (Quaestiones Geographicae, 2011)
The article presents the state of and changes in the pattern of regional disparities in Poland over the years 1995-2007. The differences in the level of economic development of regions are examined in a dynamic approach on the basis of per capita income, indices of local government finances, and investment outlays. The effect of development-activating factors on regional income is considered. An answer is sought to the question of whether the growth dynamics had a favourable effect on the evolution of regional disparities in Poland.